Synthesizing nonstoichiometric Li3−3xV2+x(PO4)3/C as cathode materials for high-performance lithium-ion batteries by solid state reaction. Issue 52 (27th June 2017) - Sun, Pingping; Su, Ningang; Wang, Yuanting; Xu, Qingyu; Fan, Qi; Sun, Yueming
Abstract : A simple solid state reaction method has been developed to synthesize nonstoichiometric Li3−3 x V2+ x (PO4 )3 /C ( x = 0–0.15) nanocomposites. Abstract : A simple solid state reaction method has been developed to synthesize nonstoichiometric Li3−3 x V2+ x (PO4 )3 /C ( x = 0–0.15) nanocomposites. Among them, Li3−3 x V2+ x (PO4 )3 /C nanocomposites with x = 0.10 exhibit the best performance, especially notable for its high-rate performance. The discharge capacity of 124.3 mA h g −1 is delivered at 20C, almost 1.5 times that of stoichiometric Li3 V2 (PO4 )3 /C nanocomposites cathode (85 mA h g −1 ). Long-life cycling performance at a high rate of 20C is also exhibited, retaining 98.3% of its original discharge capacity (124.3 mA h g −1 ) after 1000 cycles. The cyclic voltammetry and AC impedance analysis indicate that the Li3−3 x V2+ x (PO4 )3 /C ( x = 0.10) composites show the best ionic diffusivity and lowest resistance.